2017
DOI: 10.21638/11701/spbu03.2017.103
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity of topsoil layer on reclaimed and unreclaimed post-mining sites

Abstract: Topsoil layer contains various components of soil organic matter such as branches, leaves, bark, or metabolites and residues of soil biota. Soil organic matter (SOM) in forest ecosystems consists mostly of lignin, cellulose, chitin and other hydrocarbons. These compounds are decomposed mainly by soil fungi which produce extracellular enzymes to decompose wide range of organic residues. These enzymes may alter nutrient cycling and change soil properties such as water retention capacity, ion exchange capacity, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Remediation Contamination control -A physical, chemical or biological action to remove contaminants with the goals to reduce and manage the risks to human beings posed by contaminated sites. Alday et al 2011;Ličina et al 2017;Kalabić et al 2019;Hamidović et al 2020), but the most comprehensive research that has come from the European region is mainly from the Lusatian mining district in Germany (Rumpel et al 1998(Rumpel et al , 1999(Rumpel et al , 2000Schaaf et al 1999;Waschkies & Hüttl 1999;Zier et al 1999;Schaaf 2001Schaaf , 2003Wanner & Dunger 2001;Wiegleb & Felinks 2001;Wilden et al 2001;Schaaf & Hüttl 2006) and the Sokolov mining district in the Czech Republic (Kříbek et al 1998;Frouz et al 2001Frouz et al , 2007aFrouz et al , b, 2013Frouz & Nováková 2005;Šourková et al 2005a, b;Baldrian et al 2008;Helingerová et al 2010;Řehounková et al 2011;Bodlák et al 2012;Brom et al 2012;Heděnec et al 2017). In more recent years, an increasing number of publications related https://doi.org/10.17221/163/2020-SWR to reclamation sites have originated from China and, even more so, India.…”
Section: Rehabilitationmentioning
confidence: 99%
“…Remediation Contamination control -A physical, chemical or biological action to remove contaminants with the goals to reduce and manage the risks to human beings posed by contaminated sites. Alday et al 2011;Ličina et al 2017;Kalabić et al 2019;Hamidović et al 2020), but the most comprehensive research that has come from the European region is mainly from the Lusatian mining district in Germany (Rumpel et al 1998(Rumpel et al , 1999(Rumpel et al , 2000Schaaf et al 1999;Waschkies & Hüttl 1999;Zier et al 1999;Schaaf 2001Schaaf , 2003Wanner & Dunger 2001;Wiegleb & Felinks 2001;Wilden et al 2001;Schaaf & Hüttl 2006) and the Sokolov mining district in the Czech Republic (Kříbek et al 1998;Frouz et al 2001Frouz et al , 2007aFrouz et al , b, 2013Frouz & Nováková 2005;Šourková et al 2005a, b;Baldrian et al 2008;Helingerová et al 2010;Řehounková et al 2011;Bodlák et al 2012;Brom et al 2012;Heděnec et al 2017). In more recent years, an increasing number of publications related https://doi.org/10.17221/163/2020-SWR to reclamation sites have originated from China and, even more so, India.…”
Section: Rehabilitationmentioning
confidence: 99%
“…A more accurate understanding of biochemical changes occurring in soil can be achieved using a biochemical soil fertility index (M w ) that includes dehydrogenase, urease, acid and alkaline phosphatase activities, as well as soil organic carbon content 27 . Until now many studies have been conducted on the activity of soil enzymes in agricultural areas 28 , forest ecosystems, as well as on areas contaminated with heavy metals, open cast lignite mining or spoil heaps after brown coal mining 1 , 3 , 6 , 29 , 30 . However, only a few studies dealing with the activity of soil enzymes have been carried out on spoil heaps after hard coal mining 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Higher extracellular enzymes activity is associated with regions of high nutrient turnover and high primary productivity [46]. Recently, some studies have been demonstrated that metal(loid)s have an adverse influence on the activity of soil enzymes [14,47,48].…”
Section: Discussionmentioning
confidence: 99%